The Mitochondrial Antioxidant SS-31 Modulates Oxidative Stress, Endoplasmic Reticulum Stress, and Autophagy in Type 2 Diabetes - Escribano-López, Irene; de Marañon, Aranzazu M; Iannantuoni, Francesca; López-Domènech, Sandra; Abad-Jiménez, Zaida; Díaz, Pedro; Solá, Eva; Apostolova, Nadezda; Rocha, Milagros; Víctor, Víctor M (Journal of clinical medicine, 2019)
Mitochondrial dysfunction has been shown to play a central role in the pathophysiology of type 2 diabetes (T2D), and mitochondria-targeted agents such as SS-31 are emerging as a promising strategy for its treatment. We aimed to study the effects of SS-31 on leukocytes from T2D patients by evaluating oxidative stress, endoplasmic reticulum (ER) stress and autophagy. Sixty-one T2D patients and 53 controls were included. Anthropometric and analytical measurements were performed. We also assessed reactive oxygen species (ROS) production, calcium content, the expression of ER stress markers GRP78, CHOP, P-eIF2α, and autophagy-related proteins Beclin1, LC3 II/I, and p62 in leukocytes from T2D and control subjects treated or not with SS-31. Furthermore, we have evaluated the action of SS-31 on leukocyte-endothelium interactions. T2D patients exhibited elevated ROS concentration, calcium levels and presence of ER markers (GRP78 and CHOP gene expression, and GRP78 and P-eIF2α protein expression), all of which were reduced by SS-31 treatment. SS-31 also led to a drop in BECN1 gene expression, and Beclin1 and LC3 II/I protein expression in T2D patients. In contrast, the T2D group displayed reduced p62 protein levels that were restored by SS-31. SS-20 (with non-antioxidant activity) did not change any analyzed parameter. In addition, SS-31 decreased rolling flux and leukocyte adhesion, and increased rolling velocity in T2D patients. Our findings suggest that SS-31 exerts potentially beneficial effects on leukocytes of T2D patients modulating oxidative stress and autophagy, and ameliorating ER stress.